2014
DOI: 10.1021/ie503154f
|View full text |Cite
|
Sign up to set email alerts
|

New Formulations of Ni-Containing Ceramic Papers to Enhance the Catalytic Performance for the Oxidative Dehydrogenation of Ethane

Abstract: Ceramic papers composed of silica−alumina fibers structured using colloidal suspensions as binders constitute interesting materials to be used as flexible supports of catalytic materials. The deposition of Ni as the active ingredient together with Zr or Ce promoters resulted in active and selective structured catalysts for the oxidative dehydrogenation of ethane; these structured catalysts also exhibited acceptable mechanical properties. The employed binder agents (nanoparticles of ceria, zirconia, or yttria-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…This point confirms that crystalline zirconium oxide is not present, not even in the sample with a higher amount of Zr, in agreement with XRD results. Differently, at increasing Ce content in the samples, the characteristic band at 462 cm −1 of cerium oxide with fluorite-type structure appears with higher intensity in the spectra, along with two additional bands at 225 and 635 cm −1 , directly related to the CeO2 lattice defects caused by oxygen vacancies and the modification of the oxygen sub-lattice [13,25,[26][27][28][29][30][31].…”
Section: Characterization Of Active Sitesmentioning
confidence: 82%
See 1 more Smart Citation
“…This point confirms that crystalline zirconium oxide is not present, not even in the sample with a higher amount of Zr, in agreement with XRD results. Differently, at increasing Ce content in the samples, the characteristic band at 462 cm −1 of cerium oxide with fluorite-type structure appears with higher intensity in the spectra, along with two additional bands at 225 and 635 cm −1 , directly related to the CeO2 lattice defects caused by oxygen vacancies and the modification of the oxygen sub-lattice [13,25,[26][27][28][29][30][31].…”
Section: Characterization Of Active Sitesmentioning
confidence: 82%
“…It has been reported that the bands at 225 and 635 cm −1 point out the formation of a Ni-Ce-O solid solution [13], but in these samples they could also indicate that part of the zirconium is present as a Ce-Zr-O solid solution.…”
Section: Characterization Of Active Sitesmentioning
confidence: 94%
“…The structured catalysts located in a quartz reactor (Ø = 16.3 mm). The thermocouple was placed as illustrated in [28]. Particularly, the Ni-Al-M3C structured catalyst was previously wrapped with quartz wool to force the feed flow through the channels, taking into account that the outer face of the housing was not coated with catalyst.…”
Section: Catalytic Behavior In the Ode Reactionmentioning
confidence: 99%
“…Some of them offer lower pressure drop, higher energy efficiency, allow detailed designs, and ease scaling-up, among others [20,21]. The substrates that have been studied for the preparation of structured catalysts are ceramic foams [22], ceramic monoliths [23][24][25], ceramic papers [26][27][28], metallic foams [22,29], and metallic monoliths [5,30].…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic ceramic papers have been reported to be efficient for a variety of gas-phase reactions with industrial and environmental concern. Among them, reforming reactions, hydrocarbon dehydrogenation, , nitric oxide reduction, , and CO oxidation have been studied.…”
Section: Introductionmentioning
confidence: 99%